3.22 The problem of social relations in the views of Abu Nasr Farabi - Salimov Bakhriddin Lutfullaevich. Professor at Tashkent State Transport University. BABAYEV MEHRIDDIN RUZI UG‘LI. Student at Tashkent State Transport University. (Innovative technologies in construction Scientific Journal, 2023)
Аnnotation Abu Nasr Farabi also emphasizes that people living in society have different characteristics, knowledge and worldviews: "There are more or less differences and differences even in the most famous ideas of certain peoples about a certain type of people. Because every nation realizes that thing and event in its own way and reflects it. Key words: state, society, man, city, knowledge In the analysis of social relations, thinkers of medieval eastern countries also have their own views. Among scholars of this period and region, the work of Abu Nasr Farabi is well known and famous among scholars who worked on this topic. Alloma approaches the analysis of social relations from a dialectical point of view. Abu Nasr Farabi claims that there is also “the city of the ignorant - the opposite of the city of the righteous.” In this city of the ignorant, the complete opposite of all the good deeds in the city of the virtuous is accomplished. Social relations were also full of conflicts. In this city of ignorance people with all negative vices will gather. However, in our opinion, Abu Nasr Farabi should have assessed cities by the characteristics of the majority of their inhabitants. For example, a city in which there are many good people is called a city of virtuous people, and a city in which there are many bad people is called a city of ignoramuses. After all, a city of virtuous people cannot consist of 100 percent good people, and a city of ignorant people cannot consist of 100 percent bad people. Because according to ancient laws, where there is good, there is evil, or where there is evil, there is good. After all, there is no point in a life consisting only of bad things without good things. In turn, since there is evil, we value good. That is, good and evil, or in the words of Abu Nasr Farabi, virtue and ignorance are dialectically related to each other, and without one the other loses its meaning. Also, the world is created in such a way that there was, is and will be a constant struggle between these two human emotions. Abu Nasr Farabi also emphasizes that people living in society have different characteristics, knowledge and worldviews: “There are more or less differences and differences even in the most famous ideas of certain peoples about a certain type of people. Because every nation understands this thing and event in its own way and reflects it. Social relations are a very broad concept, and all things and events in social reality are part of it. One of them is the sphere of interreligious and interethnic relations. The correct establishment of these relationships is the key to stability in society. Taking this into account, the issue of religious tolerance and interethnic relations has always been the focus of attention in our independent Uzbekistan. After all, religious tolerance and the proper establishment of interethnic relations will ensure the great future of the country. Without exaggeration, we can say that the idea of religious tolerance and interethnic harmony in the Republic of Uzbekistan serves as an important factor in the development of the country. Currently, believers of 16 religious denominations and representatives of more than 130 nationalities live peacefully in our country. “They work selflessly in all areas and sectors, united for our common goal - the development of Uzbekistan, making a worthy contribution to the construction of a legal democratic state based on a developed market economy and a strong civil society.” It should be noted that issues of interreligious and interethnic relations are also analyzed in the works of Abu Nasr Farabi. Recognizing that there are representatives of different religions and nationalities in society, the great scientist says that together they can serve the development of the country: it is possible.” The above discussion shows that Abu Nasr Farabi came up with an advanced idea compared to his time thousands of years ago. Abu Nasr Farabi expressed many similar thoughts and opinions regarding the sphere of public relations, which were relevant in his time and have not lost their significance today. The origin and formation of social relations is closely connected with the history of the human community. This connection is expressed in the fact that before the advent of the community there were no social relations. First of all, a community was formed, then social relations developed. One of the greatest achievements in human history was learning to live as a community. In essence, “Every person is designed by his nature in such a way that he needs many things in order to live and achieve the highest degree of maturity, he cannot acquire these things alone, to have them, a community of people is needed... The activities of the members of such a community as a whole , it supplies each of them with what is necessary for life and attainment of maturity.” In addition to this conclusion, it can be said that community life, as an important social discovery, has raised the material, everyday and spiritual way of life of people to a much higher level. With the emergence of the community, moral, spiritual and legal procedures began to be formed that regulated living in it. These procedures radically changed the life of mankind. Did we mention this in our scientific study? Thus, the ultimate goal of all human society is happiness. So, “The essence of humanity is the achievement of true happiness, and if a person turns this goal into his highest idea and desire and thus uses all possibilities, he will achieve happiness.” As we all know, in recent years there has been and continues to be a lot of talk about the “national idea”, which should embody the aspirations of our society. In our opinion, it is appropriate not to use the phrase “national” here. Instead, it is better to call it the idea of our society or the idea of our people. A national phrase can narrow the scope of the question. Then, when forming the ideas of the people, it is necessary to abandon lofty, complex and incomprehensible slogans. Instead, we must find and promote ideas that reflect people’s real aspirations. These ideas embody noble goals in the hearts of people, and their implementation should satisfy everyone equally. Therefore, in the process of implementing these ideas, all people act as one soul. No one is watching just like an ordinary spectator. Everyone coordinates their activities as an important element of social relations. Everyone wants to live happily. Everyone wants to live a peaceful, safe and prosperous life surrounded by family and loved ones, fully enjoying the God-given blessings of life. Farobi said that “a necessary condition for a person to achieve happiness is the study of science and the acquisition of theoretical knowledge.” In our opinion, the main idea of our society should be based on these thoughts. “People want to live well today, not in the future.” That is, people and human society have always chosen the best path for themselves. “Freedom of choice is associated with will, which means that a person makes the best choice.” A person who is considered a subject of social relations has always had a choice. Considered as a system in general, this aspect extends from the life of an individual to society and even all of humanity. The development path of any system is uneven. The development path of the system consists of certain cycles, starting from certain points and continuing to new points. REFERENCES Salimov B.L. Expression of Dialectic Categories in the Individual’s Social Life // eu. International Journal of InnovativeAnalyses and Emerging Technology. Volume: 1, lssue 4, 2021. -Р.16-18. Salimov Baxriddin Lutfullaevich. The philosophical role of dialectical categories in human life. Oriental Renaissance: Innovative, educational, natural and social sciences. Volume: 1, lssue 6, 2021. -Р.406-410. Salimov Baxriddin Lutfullaevich. Prospects of Development of Communication and Transport System in Uzbekistan. WEB OF SYNERGY: International Interdisciplinary Research Journal. Volume 2 Issue 2, Year 2023 ISSN: 2835-3013. Salimov, B., Madalimov, T. (2023). Transport falsafasi. Globe Edit. Salimov Bakhriddin Lutfullaevich. The Importance of Sea Transport in the Communication System. WEB OF SYNERGY: International Interdisciplinary Research Journal. Volume 2 Issue 1, Year 2023 ISSN: 2835-3013. Salimov Bakhriddin Lutfullaevich. The Influence of the Transport and Communication System on Social Relations. Web of Semantic: Universal Journal on Ie Education. Volume 2 Issue 2, Year 2023. ISSN: 2835-3048. Salimov Bakhriddin Lutfullaevich. Reforms in the Fields of Communication and Transport and their Social Impact. Web of Semantic: Universal Journal on Ie Education. Volume 2 Issue 2, Year 2023. ISSN: 2835-3048. Салимов Б.Л. Ижтимоий муносабатларнинг коммуникация ва транспорт тизими билан детерминистик боғлиқлигининг гносеологик таҳлили. Фалсафа фанлари доктори диссертацияси. Ўзбекистон Миллий университети. Тошкент. 2022, 224 б. Salimov Bakhriddin Lutfullaevich, Tursunov, Shokhijakhan Ravshanovich, Haydarov, Mehriddin Nuriddin Ugli (2023). SYNERGETIC APPROACH IN THE ANALYSIS OF SOCIAL RELATIONS. Oriental renaissance: Innovative, educational, natural and social sciences, 3 (3), 1001-1007. Bakhriddin Lutfullaevich Salimov. NEGATIVE CONSEQUENCES OF SCIENCE AND TECHNOLOGY DEVELOPMENT. International Conference" Law, Economics and Tourism sciences in the modern world". 2023/5/1. С. 5-10.